2020
DOI: 10.3389/fmicb.2020.00942
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces lydicus M01 Regulates Soil Microbial Community and Alleviates Foliar Disease Caused by Alternaria alternata on Cucumbers

Abstract: Due to the adverse effect on the environment caused by excessive use of chemical fertilizers, the development of sustainable agriculture attracts a growing demand of biological based fertilizers composed of living microorganisms. In this study, an Actinobacteria Streptomyces lydicus M01 was isolated from the rhizosphere soil of Pyrus calleryana. This strain effectively promoted the plant growth and suppressed a foliar disease caused by Alternaria alternata on cucumbers. S. lydicus M01 exhibited growth promotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 65 publications
(66 reference statements)
2
19
0
Order By: Relevance
“…Bacillus amyloliquefaciens, B. atrophaeus, B. cereus, Pseudomonas fluorescens, etc., were demonstrated to be effective against fungal, bacterial, and viral invasion through ISR (Table 1). Recent studies suggested that beneficial microbes induce early plant ISR events (Table 1), including, but not limited to, increased expression of pathogenesis-related PR genes, enhanced activities of defense-related substances, such as phenylalanine ammonia-lyase, polyphenol oxidase, peroxidase, β-1, 3 glucanase, and chitinase, and accumulating reactive oxygen species [43,44]. PR1, PR2, and PR3 gene (antimicrobial effects, beta-1,3 glucanase, and chitinase activities); enhanced activities of phenylalanine ammonia lyase (regulation of plant growth and stress tolerance), beta-1,3 glucanase (inhibition of the mycelial growth and spore germination), and chitinase (inhibition of mycelial growth).…”
Section: Early Isr Events Induced By Beneficial Microorganismsmentioning
confidence: 99%
“…Bacillus amyloliquefaciens, B. atrophaeus, B. cereus, Pseudomonas fluorescens, etc., were demonstrated to be effective against fungal, bacterial, and viral invasion through ISR (Table 1). Recent studies suggested that beneficial microbes induce early plant ISR events (Table 1), including, but not limited to, increased expression of pathogenesis-related PR genes, enhanced activities of defense-related substances, such as phenylalanine ammonia-lyase, polyphenol oxidase, peroxidase, β-1, 3 glucanase, and chitinase, and accumulating reactive oxygen species [43,44]. PR1, PR2, and PR3 gene (antimicrobial effects, beta-1,3 glucanase, and chitinase activities); enhanced activities of phenylalanine ammonia lyase (regulation of plant growth and stress tolerance), beta-1,3 glucanase (inhibition of the mycelial growth and spore germination), and chitinase (inhibition of mycelial growth).…”
Section: Early Isr Events Induced By Beneficial Microorganismsmentioning
confidence: 99%
“…These strains can change the soil bacterial community and enhancing the disease resistance of plants. Some other studies have shown that PGPR can improve plant resistance and promote plant growth by changing soil microbial community 10,11 .…”
mentioning
confidence: 99%
“…The genus Streptomyces is the major producer of antibiotics. It plays an important role in the suppression of plant diseases induced by bacterial pathogens and has a great diversity of genes for the production of biocontrol secondary metabolites [28,29].…”
Section: Discussionmentioning
confidence: 99%